The management of NDM-β-lactamase-producing carbapenem-resistant Enterobacterales in Tuscany. (30th September 2020) - Ninci, A; Grazzini, M; Paolini, D; Niccolini, F; Mechi, M T; Righi, L; Gemmi, F; Pieralli, F; Lorini, C; Bonaccorsi, G
Abstract: Issue: An important outbreak of New Delhi metallo-β-beta-lactamase (NDM)-producing carbapenem-resistant Enterobacterales (CRE) has been reported from north-western of Tuscany since November 2018. NDM is a metallo-β-lactamase able to hydrolyze most β-lactames (including carbapenems) with limited treatment options. Description of the Problem: From November 2018 to May 2019, 7 Tuscan hospitals notified a total of 350 infected or colonized cases. This outbreak was described in a risk assessment edited by the European Centre for Disease Prevention and Control (ECDC) in June 2019. The Ministry of Health and the Tuscany Region promptly adopted infection prevention control measures. Results: Since July 2019, a regional task force, composed by experts in infectivology, microbiology and public health, coordinated the following actions: Publication of Regional Resolutions which have established practical guidelines for the outbreak management. These measures included:(I) the introduction of screening test for CRE by rectal swab for hospitalized patients; (II) the implementation of microbiological rapid molecular tests and genotyping of rectal swab; (III) the enhancement of standard and transmission-based precautions; (iv) the strengthening of handover between hospital setting and primary healthcare; (v) the implementation of a regional data-base for outbreak surveillance. Monthly regional meetings with the infection control teams of each hospital. Site visits (n. 44) performed by a group of experts in all healthcare facilities. After the implementation of these measures, a trend for decrease in positive blood cultures of NDM was registered. Lessons: The spread of NDM in Tuscany has been the opportunity to standardize and improve the approach to Multidrug-Resistant Organisms (MDROs) prevention and control. Key messages: The spread of NDM in Tuscany has been the opportunity to standardize and improve the approach to Multidrug-Resistant Organisms (MDROs) prevention and control. The cooperation among stakeholders and the standardization of precaution measures and healthcare workers' behavior allows to effectively face the MDROs diffusion.